The Impact of IFRS on Strategic Decision-Making: Are Companies Indirectly Controlled From External? - Häck, Nina (Naše gospodarstvo/Our economy, 2025)
Publicly listed companies in Europe are required to prepare consolidated financial reports in accordance with International Financial Reporting Standards (IFRS), providing a common framework that reduces the costs of international capital procurement. This study examines whether IFRS influence corporate strategic decisions or function as guiding frameworks rather than instruments of external control. A literature review identified five strategically relevant IFRS standards, complemented by structured interviews with six Austrian experts from the industrial and auditing sectors. Findings indicate that leading companies actively integrate IFRS into their strategic planning to guide financial reporting and stakeholder communication. At the same time, the standards are primarily regarded as recommendations that allow for interpretive flexibility and discretionary decision-making. The findings are not statistically representative of the Austrian market because the study aims to provide analytical and theoretical insights rather than generalisable results. The results highlight the influence of IFRS on strategy without constraining corporate autonomy, bridging accounting regulation and corporate decision-making.